Assessment of T-shape double fascia graft for lower lip deformity from facial paralysis: A questionnaire survey. Issue 3 (March 2016) - Hayashi, Ayato; Yoshizawa, Hidekazu; Natori, Yuhei; Suda, Shunichi; Mochizuki, Mariko; Nishimuta, Yuri; Tanaka, Rica; Mizuno, Hiroshi
Summary: Introduction: There are two main methods to treat lower-lip deformity (LLD) in facial paralysis. The first method is surgical intervention on the side of the paralysis, and the second involves denervating the depressor muscles on the healthy side. It is sometimes difficult for patients to ethically accept the denervating healthy tissue; therefore, we performed the T-shape double fascia graft (TSDFG), which reportedly restores symmetry. In this study, we report our experience with TSDFG and evaluation of the outcomes including the patient questionnaires. Methods: Two fascia strips from the thigh, 7 × 70 mm in size, were used; one was grafted horizontally at the lower lip to correct the static position, and the other was grafted obliquely at the lateral side by folding and crossing the horizontal fascia. A total of nine patients were treated by this procedure; three procedures were performed individually and six were performed in combination with another static or reanimation procedure. A questionnaire containing a five-point scoring system for facial appearance in multiple situations and other problems was sent to each patient at least 6 months after the surgery. Result: From the physicians' point of view, all patients achieved an improvement in symmetry of the lower lip, particularly when opening of the mouth; however, assessments from the patients demonstrated much less satisfaction. The main reason for the dissatisfaction was the slight bulkiness of the red lip. There was one comment that noted that with more treatment, the expectations were higher, and, as a result, the patient could not admit satisfaction at the end. Discussion: TSDFG is a simple and effective procedure for LLD; however, slight modifications may be required. In addition, there were some gaps in the perception of the results between the physicians and patients, and we need to consider these when planning to treat LLD.